Pengaruh Aplikasi Tandan Kosong Kelapa Sawit dan Arang Sekam Padi terhadap beberapa Sifat Kimia Tanah pada Tomat - Fitra Syawal Harahap; Hilwa Walida; Rahmaniah Rahmaniah; Abdul Rauf; Rosmidah Hasibuan; Ade Parlaungan Nasution (Agrotechnology Research Journal, 2020)
The oil palm empty fruit bunches are solid waste produced from the processing of oil palms which have a large amount of potential to be used as compost and are expected to improve the physical, biological and chemical properties of the subsoil. This study aimed to evaluate the best combination between oil palm empty fruit bunches compost and rice husk charcoal on soil chemical properties in tomato. This research was conducted in Sona Village, Labuhanbatu Regency on December 2019-March 2020. Analysis of soil chemical properties was conducted at the Socfindo Seed Production and Laboratories (SSPL) Laboratory of PT. Socfin Indonesia. The study was conducted with a factorial randomized block design with 2 factors. The first factor was the application of oil palm empty bunches which consists of no oil palm empty bunches (control), 0.5 kg/polybag, 0.7 kg/polybag and 1 kg/polybag. The second factor was the application of rice husk charcoal which consists of non-husk charcoal (control), consisting of 0.2 kg/polybag and 0.4 kg/polybag. Data that had a significant effect after analysis of variance continued with DMRT at the level of α = 5%. The results showed that application of oil palm empty fruit bunches (0.7 kg/polybag) significantly increased pH and C-organic. Application of rice husk charcoal (0.2 kg/polybag) significantly increased C-organic and P-available.